Biochar application to a fertile sandy clay loam in boreal conditions: effects on soil properties and yield formation of wheat, turnip rape and faba bean - Tammeorg, Priit; Simojoki, Asko; Mäkelä, Pirjo; Stoddard, Frederick L.; Alakukku, Laura; Helenius, Juha (Plant and soil, 2014)
Background and aims We studied the effect of different biochar (BC) application rates on soil properties, crop growth dynamics and yield on a fertile sandy clay loam in boreal conditions. Methods In a three-year field experiment conducted in Finland, the field was divided into three sub-experiments with a split-plot experimental design, one for each crop: wheat (Triticum aestivum), turnip rape (Brassica rapa), and faba bean (Vicia faba). The main plot factor was BC rate (0, 5 and 101 DM ha⁻¹) and the sub-plot factor was the N-P-K fertiliser rate. Soil physico-chemical properties as well as plant development, yield components and quality were investigated. Results BC addition did not significantly affect the soil chemical composition other than the increased C and initially increased K contents. Increased soil moisture content was associated with BC application, especially at the end of the growing seasons. BC decreased the N content of turnip rape and wheat biomass in 2010, thus possibly indicating an initial N immobilisation. In dry years, the seed number per plant was significantly higher in faba bean and turnip rape when grown with BC, possibly due to compensation for decreased plant density and relieved water deficit. However, the grain yields and N uptake with BC addition were not significantly different from the control in any year. Conclusions Even though BC application to a fertile sandy clay loam in a boreal climate might have relieved transient water deficit and thereby supported yield formation of crops, it did not improve the yield or N uptake.